Moisture Accumulation in Building Façades Exposed to Accelerated Artificial Climatic Ageing—A Complementary Analysis to NT Build 495 - Silje Kathrin Asphaug; Berit Time; Tore Kvande (Buildings, 2021)
Building façades must endure severe climatic exposure throughout their lifetimes. To prevent damage and expensive repairs, ageing tests are used in durability assessments. The NT Build 495 describes an artificial ageing procedure to address building material and component resistance to ultraviolet (UV) light, heat, water, and frost using a climate simulator. The test has been used for decades to investigate exterior surface materials and façade products but has only recently been adopted for multi-layered systems. This study investigates moisture accumulation in a façade system for retrofitting based on concrete and thermal insulation. Hygrothermal simulations of the façade system subjected to ageing were conducted. Moisture accumulation was considered theoretically for the current test procedure and compared to a modified setup in which the interior climate was controlled at 21 °C. Physical measurements were performed in the climate simulator to determine the boundary conditions. Results showed that moisture accumulation in the thermal insulation was largely affected by the type of concrete, that applying a water-repellent surface treatment reduced moisture accumulation, and that the current setup resulted in less moisture accumulation compared to the modified setup. The latter implicates accelerated degradation with the modified setup.